The Effect of the Problem Based Learning Model on Science Process Skills in Science Subjects in Class IV at the Kepong Learning Studio Malaysia - Nuristia, Wanda; Pratiwi, Indah; Basri, Amin (Universitas Pahlawan Tuanku Tambusai, 2026)
Education is an effort to improve the quality of human resources and encourage more productive individual development. This enables individuals to bring about change in their own lives and acquire the ability to contribute to society. High-quality human resources are very important for a country. Science in primary school is very important. Science has the potential to develop students’ thinking abilities, problemsolving skills, and hidden potential. The purpose of this study was to determine the effect of the problem-based learning model on science process skills in science lessons in Grade IV at the Kepong Learning Centre in Malaysia. The results of the study showed a sig value of 0.000, with Ha accepted and H0 rejected. Thus, it can be concluded that there is an effect of using the problem-based learning model on science process skills in science lessons in Grade IV at the Kepong Learning Centre in Malaysia.